The CIA and Third Force Movements in China during the Early Cold War : the Great American Dream - Jeans, Roger B. (Lexington Books, 2017)
This study examines the CIA's ""third force"" strategy-providing support for a third-party alternative over two primary on-the-ground options-in East Asia during the first decade of the Cold War. The author argues that the strategy failed due to a lack of understanding of the historical and cultural contexts of the region.